Anti-hyperglycaemic activity of the leaves of Tetracera Scandens Linn (dilleniaceae) in Alloxan induced diabetic male albino wistar rats - Ahmed, Qamar Uddin; Umar, Abdulrashid (2010)
This study was designed to explore the anti-diabetic effect of the leaves of Tetracera Scandens Linn. Merr., (T.Scandens L.) (family: Dilleniaceae) (local name: Mempelas kasar) in vivo. Different parts of this plant are used traditionally in the treatment of gout, internal pains, sore throat, hepatitis and lowering hypertension. Glucose levels in rats with hyperglycemia induced by alloxan [150mg/kg body weight (b.w.)] were determined after the oral administration of dichloromethane, ethylacetate, and butanol fractions of the leaves of T. scandens L. Dose (500mg/kg b.w.) was administered to both normal and alloxan induced diabetic rats. The highest blood glucose lowering effect was found to be in butanol fraction, followed by ethylacetate and dichloromethane. However, in normal rats no hypoglycemic activity was observed in all the administered fractions when compared with both diabetic and normal controlled groups. The fall of blood glucose was also found to be comparable to that of the effect produced by a standard anti-diabetic drug, glibenclamide (0.6mg/kg b.w.). Phytochemical screening explicitly confirmed the presence of terpenoids and flavonoids in all extracts which collectively might be responsible for its significant anti-hyperglycemic effect. In conclusion, the butanol extract possesses strong antidiabetic activity in comparison to that of ethylacetate while the least activity was exerted by DCM fraction, hence, T. scandens L., could be screened further with respect to finding out its medicinal efficacy particularly towards the treatment of chronic diabetes mellitus. This laid the foundation to study the active compounds of this plant which are responsible for the anti-hyperglycemic activity.